Kajian Determinan yang Berhubungan dengan Status Gizi Kurang pada Balita - Dewi Ayu Ningsih (Universitas Mitra Indonesia, 2022)
Nutritional problems in Indonesia that need attention are undernutrition and overnutrition (double burden). In Indonesia, malnutrition is still the most common case and often occurs in under five children. Malnutrition has a significant impact on a health status. The data showed the prevalence of under-five children with sever wasted, wasted, and overweight in Indonesia were 3.9%, 13.8%, and 3.1%, respectively. Malnutrition problems in Lampung Province were under five children with sever wasted of 3.1%, wasted of 12.8%, and overweight of 2.8%. Malnutrition of under five children cases in Bandar Lampung City were found to be 3.02% of severe wasted and 13.07% of wasted. The data illustrates that the cases of under five children with malnutrition both nationally and locally are still high. Wasted was caused by many factors including nutrition, infectious diseases, and social factors. Undernutrition on under five children if not immediately intervened properly shall provided a great opportunity for children's nutritional status to fall into a worse condition, namely severe wasted, and so on will be a manifestation of stunting in under five children. The purpose of this scientific study was to determine the determinants associated with undernutrition status in under five children. Keywords : Nutrisional status of under five children, Malnutrition, Wasted